SORPTION AND STUDY OF IONS OF Cu(II), Zn(II) AND Ni(II) IN SYNTHESISED SORBENT BASED ON UREA, FORMALDEHYDE AND DIPHENYLCARBAZONE (Scientific journal of the Fergana State University, 2025)
This article synthesized a nitrogen-containing chelating sorbent based on the cross-polycondensation reaction of urea and formaldehyde with diphenylcarbazone (UF-DC) in an alkaline environment. The effect of temperature on the polycondensation process of the synthesized UF-DC was studied. The optimal temperature for polycondensation was chosen as 363 K, and the duration of the reaction was 1,5-2 hours, the static exchange capacity for 0,1 N NaOH solution was 4,3 mg-eq/g. 0.1:0.2 0.3 mol ratios of urea, formaldehyde (2:5), and diphenylcarbazone were taken for the chelating sorbent, and the levels of sorption with Cu (II), Zn (II), and Ni (II) were determined. The influence of the environment on the sorption process of KF-DK with Cu (II) ions was analyzed. Based on the results of IR spectroscopic analysis, the approximate structure of the newly synthesized sorbent was proposed.